MONITORING AND CONTROL SYSTEM OF IOT-BASED GAS LEAK DETECTION - Muliawati, Fithri; Mustopa, Opa (JUTEKS, 2020)
LPG gas leaks are one of the factors causingfires in housing, this is due to gas leaks notbeing able to be detected from the start becausethe gas content is usually small and notsmellable, when there is a lot of gas outside thecylinder and there is a trigger or sparks aroundit, the fire does not occur. it is undeniable that itwill happen. So that this can be avoided, amonitoring and control system for IOT-basedGas Leak Detection is created, by detecting lpggas leaks by operating the MQ-06 sensorreading which has been set at a set point of 1960ppm, with a maximum sensor reading limit of10,000 ppm based on Arduino nano 10 bit withinformation transmission media in the form ofthe NodeMcu V3 module.The results of the MQ-06 sensor readings areprocessed in the Arduino program so thatinformation is generated in the form of soundnotifications generated by the buzzer, when theMQ-06 sensor detects LPG gas at a set point of1960 ppm the sensor will send data in the formof an analog voltage sent to Arduino andconverted into a digital voltage through theADC facility to then send information, thesensor will send data to Arduino to be managedin the Arduino IDE software so that it canrespond in the form of a buzzer as an alarm,displays information on the LCD and activatesthe exhaust fan, and this tool can also sendinformation gas analog data to androidsmartphones using the Blynk platform via theinternet network